Sinkronisasi Program Bantuan Langsung Tunai (BLT) antara Pemerintah Desa dan Pemerintah Pusat di Desa Marindal II - Talita Sembiring; Kania Nova Ramadhani; Gadis Prasiska Sembiring; Julia Ivanna (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to determine the synchronization mechanism carried out in the implementation of the Village Fund Direct Cash Assistance (BLT) Program between the central government and the village government in Marindal II Village. This research used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of the BLT program was carried out with a systematic coordination mechanism between the central and village governments, starting from coordination meetings, data collection by the hamlet head, verification, to direct and transparent distribution of assistance. This finding shows that synchronization between the central and village governments in the distribution of BLT can be effective if supported by good coordination, understanding of regulations, and transparent communication to the community.